Origem e organiza????o do sistema de ensino e as pol??ticas de forma????o docente no estado de Roraima - Oliveira, Sebasti??o Monteiro (2016)
This paper presents the results of a research that had as its object of study Roraima State educational system, its challenges, difficulties, progress, setbacks and primary education teacher training policies. The text presents data from 1945 to 2015, occasionally referring back to 1890, when the city of Boa Vista was created. The central part of the research rests on the actions taken to solve the lack of teachers for basic education problem during that period. The research is descriptive and analytical and favors the data collection and the actions taken in the process of organizing Roraima education system, specially related to primary education teacher training policies. In this purpose, it uses bibliographic and documentary research aiming to organize the large amount of existing dispersed data. Newspaper articles from different eras, and testimonials of people who participated in this process, and images of the surveyed periods - obtained in state newspapers- and public archives and the author???s collection, and data extracted from different official bases - such as INEP, UFRR, the UERR and IBGE - were used as a primary sources. This set of data and information allowed for a broad mapping from the early education initiatives in 1890 to the current conditions of education in the state. The data obtained allow us to state that the process of creation and organization of the education system undergoes through changes as the political status of the region changes, from village to Territory and finally to State of the Federation in 1988. In this long process, teacher training has always been the central problem and an impediment to the expansion of the education system. A wide range of actions is presented in the text, mostly of emergency and temporary nature, put in practice to solve this issue. Only in the 1970s, with the emergence of the first higher education offers, teacher training opportunities begins to diversify and increase. This research shows that the proliferation of public and private institutions of higher education equated only partially this situation because while it presents a data growth in the number of teacher training openings for basic education, teachers' working conditions are substandard with scrapped schools, the devaluation of professional education, problems with teaching career, etc. This work also shows the status of vocational education, which has expanded the offer, specifically after the creation of a school belonging to the Federal Network of Technological Education. It analyzes recent Roraima educational data, especially after the creation of IDEB. Although the data collected show very positive numbers, the same data shows that much remains to be done. The research sought to uncover aspects of education in this part of the Amazon, through the description of basic education, and higher education, and vocational education offer, permeated by teacher training policies.